Comparison of the Effects of Omeprazole and Rabeprazole on Ticlopidine Metabolism In Vitro - Yuichi Kinoshita; Naoki Matsumoto; Minoru Watanabe; Yuko Takeba; Yutoku Yoshida; Keiichiro Ohba; Satoshi Suzuki; Fumio Itoh; Toshio Kumai; Shinichi Kobayashi (Elsevier, 2011)
Abstract.: The thienopyridine derivative ticlopidine (TCL) is an inhibitor of adenosine diphosphate-induced platelet aggregation. Combination therapy with a thienopyridine derivative and aspirin is standard after coronary stenting, although more hemorrhagic complications occur with the combination therapy than with aspirin alone. A proton pump inhibitor (PPI) is required for prevention or treatment of upper gastrointestinal bleeding in such cases. We examined the effects of PPIs [omeprazole (OPZ) and rabeprazole (RPZ)] on TCL metabolism using pooled human liver microsomes prepared from various human liver blocks and 12 individual human liver microsomes. We calculated the Ki values of each PPI for TCL metabolic activity and compared the inhibitory effect of each PPI on TCL metabolism. The Ki values of OPZ and RPZ were 1.4 and 12.7 μM, respectively. The inhibitory effect of OPZ (78.6 ± 0.05%) was significantly greater than that of RPZ (24.2 ± 0.05%) (P < 0.001). Interestingly, a negative correlation existed between the inhibitory effect of OPZ and CYP2C19 activity (r = −0.909, P < 0.001). These results suggest that the inhibitory effect of OPZ is more potent than that of RPZ in vitro. In conclusion, RPZ appears preferable when administering TCL, aspirin, and a PPI in combination. Keywords:: ticlopidine, proton-pump inhibitor, drug-drug interaction, clopidogrel, cytochrome P450 (CYP) 2C19